Brake by wire control with pedal feedback and brake boost - W. A. Shanaka P. Abeysiriwardhana; A. M. Harsha S. Abeykoon (Bulletin of Electrical Engineering and Informatics, 2021)
"By wire" technology merged into multiple vehicular subsystems, including gear changing, drive, and braking systems. The brake by wire system is developed to overcome the problems associated with the integration of mechanical and hydraulic systems in novel vehicular systems. Even though brake by wire systems has potential advantages, the conventional brake systems' tactile sensation will be removed if migrated to the electrical by wire control scheme. This paper proposes a novel control mechanism that provides amplification of force, scaling of position replication, and a virtual spring-damper based pedal retraction which provides bilateral brake force feedback to the driver's pedal similar to the hydraulic brake system. The proposed system performance was simulated and tested using a bilateral teleoperation system with disturbance observers (DOB) and reaction force observers (RFOB). The proposed system provides pedal force amplification and brake force feedback to the driver's pedal using RFOBs. The virtual spring retracts the brake pedal, similar to a mechanical pedal retraction system. The system simulation and experimental results provide evidence of the proposed system's force amplification, position scaling, and pedal reaction capabilities.